Role of linear endosonography in the diagnosis of biopsy‐negative malignant esophageal strictures: Exploring the unexplored. Issue 2 (18th July 2019) - Dahale, Amol S; Srivastava, Siddharth; Sonika, Ujjwal; Dalal, Ashok; Goyal, Aditi; Sakhuja, Puja; Sachdeva, Sanjeev; Puri, Amarender S
Abstract : Background and Aim: Endoscopic biopsy is standard for the diagnosis of esophageal malignancy. However, few cases present with smooth stricture with repetitive negative biopsy results. We aimed to use linear endoscopic ultrasound (EUS) and fine‐needle aspiration (FNA) in the diagnosis of biopsy‐negative suspected malignant esophageal strictures. Methods: We retrospectively analyzed the data from August 2017 to December 2018 of biopsy‐negative esophageal strictures. All adult patients with twice‐negative biopsies and with smooth overlying esophageal mucosa on endoscopy were included. Clinical, epidemiological, endoscopic, imaging, and EUS findings were noted and analyzed. Results: Eighteen patients underwent EUS for suspicion of malignant esophageal stricture. Seven were excluded as they were submucosal tumors. Eleven patients showed the presence of malignancy on EUS FNA samples. Nine were males. Computed tomography showed esophageal wall thickening in eight (16–38 mm) and esophageal mass in three patients. EUS showed loss of a normal five‐layered wall structure of the esophagus in all patients. Fine‐needle aspiration cytology demonstrated squamous cell carcinoma ( n = 4), adenocarcinoma ( n = 4), poorly differentiated carcinoma ( n = 2), and neuroendocrine carcinoma ( n = 1). There were no complications. Conclusion: EUS with FNA is effective and safe for the diagnosis of biopsy‐negative malignant esophageal strictures. Abstract : Esophageal malignancy presenting as smooth esophageal stricture with a negative biopsy for malignancy is not uncommon. We retrospectively analyzed the data of 11 such patients who appeared to have malignant esophageal stricture otherwise but had negative repetitive biopsies. Linear endosonography provided a safe and effective modality for diagnosis in such patients.